Inherited Wounds: Intergenerational Trauma in Kavita Daswani’s Everything Happens for A Reason (Literary Voice, 2025)
This research paper explores the theme of intergenerational trauma in Kavita Daswani’s Everything Happens for A Reason through Jeffrey C. Alexander’s Cultural Trauma Theory. Centering on the protagonist, Priya, the study examines her family dynamics and cultural expectations to understand how collective traumatic experiences are transmitted across generations. The analysis highlights the emotional and psychological impacts of inherited trauma on Priya’s identity and mental health, particularly how family secrets and unspoken histories perpetuate these struggles. The paper delves into the cultural and societal pressures that Priya faces, emphasizing the conflicts arising from traditional values and modern aspirations. Additionally, it investigates Priya’s journey toward healing and reconciliation, showcasing her efforts to address and overcome the cycle of trauma. By applying Cultural Trauma Theory, this study offers a nuanced perspective on how cultural and societal factors shape personal histories and resilience, contributing to literary scholarship, psychology, and cultural studies.
Keywords: Intergenerational Trauma, Identity, Family Dynamics, Cultural expectations, Societal pressures